Decentralized Finance: Development of a taxonomy to support regulatory measures - Michel Wagner; Nicolai Krüger; Markus Kleffmann; Frank Teuteberg (IU Internationale Hochschule, 2024)
Amidst rapid developments in digital financial technologies, the need for effective Decentralized Finance (DeFi) regulation is at the center of discussions. This paper aims to develop a comprehensive taxonomy for DeFi that brings to the forefront the diverse structures and characteristics of protocols and applications and can serve as a basis for developing regulatory policies. A detailed analysis of 144 DeFi projects is conducted using a qualitative research approach with inductive methodology. Based on the analysis, a taxonomy has been developed, which can be used to assist in the design of regulatory policies. From this taxonomy, five ideas are derived which could serve as a potential basis for designing future regulatory measures. In doing so, the work highlights the need to develop appropriate regulations for the DeFi market, which has been mainly unregulated to date. The findings highlight the need for increased international cooperation among countries to achieve a uniform regulatory regime that accommodates the DeFi industry's dynamic developments. The taxonomy approach developed in this research may prove to be a critical tool to foster this international cooperation and promote uniform regulation.
Keywords: 004; Blockchain; DeFi; Regulation; Taxonomy; Decentralized Finance; Dapps